Potencialidades e limitações na gestão do Plano Individual de Trabalho em Bibliotecas Setoriais da Universidade Federal da Paraíba - Silva, André Domingos da (2018)
The history of organizations is marked by stages experienced according to the demands of their time, in the sense of leading them to achieve results that satisfy their audience of interest satisfactorily. In this perspective, management through planning and management strategies in organizations has a fundamental role in achieving results, managing routines and processes that meet these demands. Thus, the objective of this research was to analyze the main potentialities and limitations identified by the directors of the sectoral libraries in the management of the Individual Work Plan (PIT) of the technical-administrative servers of the Sectorial Libraries of the Federal University of Paraíba. Specifically, it was sought to identify the documents guiding the process of management of the Individual Work Plan of the servers of the Sectoral Libraries of the UFPB; understand the understanding of the directors of the sectoral libraries in relation to the management of the ITP; verify the control and evaluation of the goals established in the Individual Work Plan; and propose an instrument applicable to the management of the Individual Work Plan of the administrative technical servers of the Sectoral Libraries of the UFPB. It was characterized as a descriptive and exploratory case study with a qualitative approach, and data collection was carried out in institutional documents such as the Institutional Development Plan (PDI), the PIT and the Performance Per Skills System (SGDCom) primer, and also through the application of a questionnaire, with closed and open questions. The technique used to treat the collected data was the Bardin content analysis. As a result, it was noticed that the majority of the directors see the PIT in a positive way, and that serves as a facilitator instrument in the management of the individual competencies of the servers, both in the identification of their potentialities and the difficulties and limitations of each one. But on the other hand, there are occasional opinions about the underutilization of PIT, not seeing in the tool the potential management of people that it can provide to the work sector. They also understand that PIT makes it possible to identify individual competencies, manage daily activities, and also identify the limitations that occur in the performance of each server. The main disadvantage was the lack of a tool that assists in the execution and evaluation of the established goals. As a support tool, the 5W2H Action Plan is suggested as an instrument for the auxiliary control of the PIT, in order to contribute to the achievement of the goals individual, sectoral and institutional.